Determinan Loyalitas Pelanggan E-Commerce pada Mahasiswa Organisasi Kemahasiswaan di Surabaya: Peran Digital Marketing, Social Media Engagement, dan Customer Trust - Elias Yosman Moma; Gogi Kurniawan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of digital marketing, social media engagement, and customer trust on e-commerce customer loyalty among university students involved in student organizations in Surabaya. This study uses an explanatory quantitative approach with data collected through a Likert-scale questionnaire distributed to students who are active in student organizations and have experience transacting on e-commerce platforms. The data was analyzed using multiple linear regression with the help of SPSS. The study results show that digital marketing has a positive effect on customer loyalty, meaning that promotional content, personalized messages, and easy access to information can encourage repurchase intentions. Social media engagement also has a positive effect because interactions, reviews, comments, and social recommendations strengthen customers' connection with the platform. Customer trust is an important determinant because student loyalty largely depends on perceptions of transaction security, clarity of information, platform reputation, and fulfillment of service promises. Simultaneously, these three variables form the foundation of e-commerce customer loyalty among college students involved in organizations. This finding implies that e-commerce managers need to integrate digital marketing strategies, strengthen social media interactions, and build trust to retain young customers who are critical, socially connected, and responsive to digital experiences. The contribution of this research lies in positioning organizational students as a segment of digital consumers influenced by community dynamics, social media intensity, and rational evaluation of online transaction risks.